Pelaksanaan Isbat Nikah di Pengadilan Agama Pandeglang - Ahmad Sanusi (Universitas Islam Negeri Jakarta, 2016)
This study shows that the implementation of marriage stipulation in the Religious Pandeglang is similar to other religious courts, in accordance with the procedure of the legislation. Based on the data, isbat nikah in the Religious Court of Pandeglang has increased annually. In 2012, the number of isbat nikah amounted to 41 cases and in 2013 increased to 68 cases, then in 2014 became 135 cases. Isbat nikah established by the Religious Courts Pandeglang is a marriage that has already met the requirements of marriage but has not recorded yet because of poverty. Therefore, isbat nikah is free of charge.DOI: 10.15408/ajis.v16i1.2901